Analysis of Vegetation Changes After the 2023 eruption of Mount Marapi in Google Earth Engine - Hamdy Arifin; Pakhrur Razi; Yuta Izumi (GeoREST, 2026)
The eruption of Mount Marapi in late 2023 caused substantial environmental disturbance, particularly to vegetation cover on its slopes and surrounding areas. Ashfall and pyroclastic deposits reduced vegetation health by covering leaf surfaces and disrupting photosynthetic activity, yet the spatial extent and severity of this impact have not been systematically quantified. This study analyzes vegetation changes before and after the eruption using the Normalized Difference Vegetation Index (NDVI) and Normalized Burn Ratio (NBR) derived from Sentinel-2 imagery processed on the Google Earth Engine (GEE) platform. The analysis covers a 35 km radius from the crater, comparing a pre-eruption period (1 November–22 December 2023) with a post-eruption period (24 December 2023–20 February 2024). Results reveal a marked decline in mean NDVI from 0.58 to 0.33 and mean NBR from 0.56 to 0.29, corresponding to approximately 43% vegetation degradation attributable to volcanic activity. Spatial analysis of ΔNDVI and ΔNBR further indicates that 45–50% of the slope area experienced moderate to severe damage, concentrated on the east and southeast flanks, consistent with the dominant direction of ash dispersal, whereas the foothill zones showed early signs of vegetation recovery within two months. These findings confirm that cloud-based multi-temporal Sentinel-2 processing on GEE offers a rapid and reliable approach for post-eruption vegetation monitoring, providing a quantitative basis for land rehabilitation planning and environmental risk management in volcanic disaster-prone regions.